2016
DOI: 10.1016/j.annemergmed.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

STONE PLUS: Evaluation of Emergency Department Patients With Suspected Renal Colic, Using a Clinical Prediction Tool Combined With Point-of-Care Limited Ultrasonography

Abstract: Study objective-We determine whether renal point-of-care limited ultrasonography (PLUS) used in conjunction with the Sex, Timing, Origin, Nausea, Erythrocytes (STONE) clinical prediction score can aid identification of emergency department (ED) patients with uncomplicated ureteral stone or need for urologic intervention.Methods-This was a prospective observational study of adult ED patients undergoing computed tomography (CT) scan for suspected ureteral stone. The previously validated STONE score classifies pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
90
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 27 publications
9
90
2
1
Order By: Relevance
“…The finding of hydronephrosis on renal point-of-care limited ultrasonography was shown to have a sensitivity of 66% and specificity of 58% for urologic intervention; moderate to severe hydronephrosis had a modest specificity (86%), but the sensitivity was diminished (36%). The addition of renal point-of-care limited ultrasonography modestly improved risk stratification of the STONE score [31]. Age and elevated white blood cell count are known predictors of ureteral stone requiring urologic intervention [17,32].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of hydronephrosis on renal point-of-care limited ultrasonography was shown to have a sensitivity of 66% and specificity of 58% for urologic intervention; moderate to severe hydronephrosis had a modest specificity (86%), but the sensitivity was diminished (36%). The addition of renal point-of-care limited ultrasonography modestly improved risk stratification of the STONE score [31]. Age and elevated white blood cell count are known predictors of ureteral stone requiring urologic intervention [17,32].…”
Section: Discussionmentioning
confidence: 99%
“…We chose to perform follow up at 30 days based on the recommended trial of medical expulsion therapy of 4–6 weeks 8,10,41,42. Two prior studies found moderate and severe hydronephrosis to be more predictive of the need for urologic intervention 17,32. A smaller prospective study analyzed the test characteristics of severity of hydronephrosis and stone size >5mm on risk of 30-day hospitalization in renal colic patients and found any hydronephrosis to be 100% sensitive and 44% specific 31.…”
Section: Discussionmentioning
confidence: 99%
“…However, as many as 50% of patients diagnosed with renal colic will have recurrent episodes and may receive multiple CTs throughout their lifetime, adding to costs, increased length of stay, and radiation exposure 1013. There are currently no validated practice guidelines for the diagnosis and ED management of renal colic; thus, the need for a multidisciplinary approach to managing this disease is clear 12,1417…”
Section: Introductionmentioning
confidence: 99%
“…If CT is desired to delineate stone size and location, this is an optimal population for reduced-dose CT. 8 High likelihood of ureteral stone has been consistently associated with low likelihood of alternate diagnoses in the initial retrospective, prospective, and external validations. [2][3][4][5]7 The recent editorial also raised the question of whether risk stratification is necessary when a clinician believes that a CT scan is warranted. That is precisely when risk stratification is needed: when the clinician is about to press the "order" button.…”
mentioning
confidence: 99%